Studi Prospek Monasit di Daerah Tumbang Rusa, Tanjung Pandan, Belitung, Propinsi Bangka Belitung - Soetopo, Bambang; Subiantoro, Lilik; Ngadenin, Ngadenin; Madyaningarum, Nunik (EKSPLORIUM, 2011)
Monazite mineral chemically contained U, Th and rare earth elements (REE) that geologically associated with the presence of zircon as plaser beach and river sediments. Distribution of granite that containing monazite lays on a single point lead Malaysia, Bangka Belitung, Karimata. The content of monazite sands in concentrate reached 2.719% is in the granite contain monazite 1-2%. The purpose of this research are expected to get the geological character of information acquisition, distribution and potentially resource of Monazite in the10 km2 area​​. The method taken are the radioactivity measurement of rocks and sediment, heavy mineral sampling and laboratory analysis, including grain size analysis and the levels of U, Th and RE.The Results of research showed that, in geological rock formation composed of Carbon-old klampit - Perm who have metamorfosed and unbreakable then intrusived by granite Triassic - Jurassic containing monazite, zircon. Due process of weathering, sedimentation of mineral monazite, zircon separated and deposited as alluvial scattered trending NW - SE, which is reflected from the measurement data alluvial radioactivity ranged from 75-400 c / s. U concentration ranges from 9.5 to 76.5 ppm U and Th content of 55-610 ppm Th with the prospect area 399.3 Ha.